Cryoballoon pulmonary-vein isolation for atrial fibrillation with heart failure: results from a single-center cohort. (25th November 2020) - Boehmer, A; Rothe, M; Jaqubi, S; Summ, A; Soether, C; Abboud, J; Ringwald, V; Dobre, B; Kaess, B; Ehrlich, J
Abstract: Background: Atrial fibrillation (AF) and heart failure (HF) are of growing prevalence and increasing mortality. Radiofrequency ablation is safe and effective for patients with AF and HF. Prognosis might be improved in patients treated. However, there is no prospective trial investigating efficacy and safety of cryoballon ablation in patients with AF and HF. Objective: To prospectively compare cryoballoon ablation in patients with and without HF (defined as LVEF ≤40%) in terms of safety and efficacy. Methods: Ongoing POLAR-HF trial is a prospective, investigator-initiated, single-center, non-inferiority, open-label study. We analyzed 244 consecutive patients who underwent cryoballoon ablation. Of these 217 had normal LVEF (age 68.1±9.6 years, CHA2DS2-VASc Score 2.5±1.3, 55.3% male) while 27 patients (11%) suffered from HF (age 70.4±8.6 years, CHA2DS2-VASc Score 3±1.2, 70.4% male). Follow-up was performed at 3, 6 and 12 months after ablation. Kaplan-Meier method was used to calculate 12-month event-rate estimates. Log-Rank Test to estimate hazard ratios in the primary analysis. Endpoints were: symptomatic AF relapse for efficacy and bleeding, stroke or death for safety. Results: Analysis showed no difference in AF-free survival rate between patients with and without HF (81% vs. 76.3%, Log-Rank-Test P=0.81, Figure). Primary safety end point occurred in 5 patients with normal LVEF (2.3%) and none in the HF-group. No deaths were observed. Conclusion: Results of POLAR-HF indicate that cryoballoon ablation is an effective ablation method for patients suffering from AF and HF. Funding Acknowledgement: Type of funding source: None